The Fundamental Power of the Soul in Kant’s Reflections on Genius: Between the Influences of Tetens and Sulzer - Sánchez-Rodrígez, Manuel; Secundant, Sergii (Sententiae, 2025)
In the Critique of Pure Reason, Kant addresses the problem of reason’s supposition of a fundamental power underlying the faculties of cognition. This concept had been debated in seventeenth- and eighteenth-century philosophy. Kant’s position in this work is not entirely clear, although a distinct dependence on Tetens’s prior treatment of the issue can be detected. The requirement to assume a unitary foundation underlying the diversity of the mind’s operations or faculties was a common theme in Leibnizian-Wolffian philosophy. In this article, we will argue that Kant developed the concept of a fundamental power primarily through his theoretical elaborations on the nature of genius. In this way, he integrates this concern of the Leibnizian-Wolffian tradition into his aesthetic project.